Upaya Preventif Berkembangnya Money Game di Indonesia - Harizan, Harizan (FAKULTAS SYARIAH DAN EKONOMI ISLAM IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2017)
Based on the fact lately, there were some methods of seeking treasure in social life nowadays. One of them was Money Game (the term of Money Game actually never found in any encyclopedia neither Wikipedia, but found only for interpretation of Ponzi Scheme Business), through members’ or investors’ recruitment. They were promised getting profit from their membership and investment, more than any bank even conventional or sharia banking ever promised. The last case of Money Game method was Dream for Freedom (D4F), found in year 2015 and ended in April 2016. The founder offered the extra ordinary profit and benefit, such as 1% profit per a day from member’s investment. This condition successfully recruited hundred thousands of members, from the low rank of education to the high one. Indonesian’s Government such as the Financial Services Authority (OJK) actually has been preventing the people from being victims and spreading of Money Game’s methods, but still the founder of any Money Game find the way to eliminate those preventing ways. Therefore Government has to try another way, through involving another institutional, even government’s Institutional or Social’s Institutional and organizations.